Megafauna in Salt Marshes - Gaskins, Leo C.; Paxton, Avery B.; Silliman, Brian R. (Frontiers in Marine Science, 2020)
Megafauna shape ecosystems globally through trophic interactions, ecology of fear, and ecosystem engineering. Highly productive salt marshes at the interface of terrestrial and marine systems have the potential to support megafauna species, but a recent global meta-analysis of consumer-plant interactions in marshes found few studies investigated impacts of wild megafauna. We conducted a literature review to document the variety of megafauna in salt marshes and found that 34 species utilize salt marshes, including sharks, manatees, pinnipeds, crocodilians, sea otters, hippos, and large terrestrial animals, such as lions, bears and water buffalo. The use of salt marsh habitats by a variety of megafauna may have implications for both the conservation of these large consumers and for the resilience of coastal wetlands through stabilizing feedbacks on plant ecosystems. Future studies should quantify the occurrence and impacts of megafauna in salt marshes, and how their conservation can help restore these valuable ecosystems.